Evaluation of the direct and indirect impact of the COVID-19 pandemic in Tuscan nursing homes. (20th October 2021) - Scardina, G; Collini, F; Mazzilli, S; Forni, S; Privitera, GP; Tavoschi, L
Abstract: Background: Residents in long-term care facilities (LTCFs) are at higher risk of contracting and developing serious outcomes from COVID-19. Despite the media attention and the specific survey launched by the Istituto Superiore di Sanità, official data on Italian LTCFs are scarce. The objective of our study was to provide an estimate of the direct and indirect impact of COVID-19 in Tuscan LTCFs by assessing the rate of hospital admissions and the overall mortality rate among LTCF residents in 2020, comparing them with those observed in the period 2018-2019. Methods: For the analysis two regional administrative data flows were linked. The first one providing data on the number of LTCFs residents - and deaths - affiliated with the regional health system, while the second on hospital discharges. The monthly hospitalization and mortality rates for 2020 were compared with those of the two previous years. Results: The number of residents in LTCFs decreased significantly (-10.4%) and consistently in 2020 compared to the average of the previous two years. The rate of total admissions decreased slightly in 2020 (32.5%, -8.2% compared to 2018/19). However, excluding admissions due to COVID-19, the reduction was more pronounced (-21.9%), with large monthly variations (-33% and -43% in March and November 2020) statistically significant (RR2020/2018-19=0.66 and 0.57; 95%CI: 0.57-0.77; 0.48-0.68). A total of 581 admissions for COVID-19 occurred in 2020, with a monthly average of 0.6% and two peaks observed in April and November (1.86%; 1.82%). The overall mortality rate increased by 31% (2018/19= 18.6%; 2020= 24.4%), with a maximum (+201%) in November 2020 (RR2020/2018-19=3.01; 95%CI: 2.5-3.56). Conclusions: The impact of the pandemic on Tuscan LTCFs in terms of deaths and patient care by hospitals has been considerable, with the greatest reduction in hospital admissions occurring mostly in the months characterised by the highest mortality rate and admissions for COVID-19. Key messages: The direct and indirect impact of the pandemic on Tuscan LTCFs has been considerable, probably due to the reorganisation of LTCF services and limited coordination with hospital health care. The greatest reduction in hospital admissions, especially those not COVID-related, occurred mostly during the months characterised by the highest mortality rate and admissions for COVID-19.